AUTOMATIC LIGHTING CONTROL IN HYDROPONIC FARMS - BARANOVSKYI, VIKTOR; BORETSKA, TETYANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article examines the impact of automated lighting systems on plant growth and development under hydroponic conditions. Modern technologies for controlling lighting parameters, which ensure the optimization of photosynthetic processes and increase crop yields, are considered.Key lighting characteristics such as light intensity, spectral composition, photoperiod, and uniform distribution of light energy are analyzed. Special attention is given to the use of light-emitting diode (LED) sources, which allow precise spectrum adjustment for different plant growth phases, reducing energy consumption and enhancing the efficiency of light radiation.The principles of operation of automated lighting systems are studied, including the use of light, humidity, and temperature sensors, microprocessor controllers, and programmable algorithms for dynamic regulation of the lighting environment. The role of artificial intelligence and Internet of Things (IoT) technologies in creating intelligent control systems that adapt lighting according to plant needs in real-time is described.The article presents a comparative analysis of traditional and modern lighting systems, including incandescent lamps, fluorescent, and LED light sources. The advantages of integrating automated solutions into hydroponic farms are highlighted, such as reduced energy costs, increased crop yields, decreased need for manual control, and the creation of a stable microclimate for plant cultivation.Special attention is given to the prospects for developing automated lighting control in hydroponic systems, particularly the implementation of machine learning technologies, predictive analytics, and adaptive LED systems that can adjust the spectrum and intensity of light depending on the plant's condition.The research results demonstrate the significant potential of automated lighting systems in improving agricultural production efficiency, making them a promising direction for the development of modern agrotechnologies.
Keywords: energy efficiency; plant mass; leaf area; root system; hydroponic method; vegetable crops; installation; substrate; mineral solution; hydroponics; photosynthesis; sensors; controllers